Implementation of The Problem Based Learning Model Using The "Pancasila Smart Board" Medium to Improve Student Learning Outcomes in The Pancasila Education Subject Topic: Pancasila Values for Grade Iii at Sdn Ta-mansari 1 - Delfi Riski Anjana; Ribut Prastiwi Sriwijayanti; Shofia Hattarina (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study examines the implementation of the Problem-Based Learning model using the "Pancasila Smart Board" medium to improve student learning outcomes in the Pancasila Education subject—specifically regarding Pancasila values—for third-grade students at SDN Tamansari 1. The study was motivated by low student learning outcomes regarding Pancasila material at the elementary level and a teaching process dominated by the lecture method, which resulted in low student engagement. The objective of the study was to describe the implementation of the instructional medium and to improve student learning outcomes. A classroom action research method was employed, conducted over two cycles with 16 students as subjects. The results demonstrated an improvement in learning outcomes, with the average rising from 37.5% in the pre-cycle stage to 56.25% in Cycle 1, ultimately reaching 93.75%. It can be concluded that implementing the Problem-Based Learning model using the Pancasila Smart Board medium effectively improves the learning outcomes of third-grade students at SDN Tamansari 1.